2022
DOI: 10.1111/aos.15151
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare expenditure of intravitreal anti‐vascular endothelial growth factor inhibitors compared with dexamethasone implant for diabetic macular oedema

Abstract: Purpose: The aim of this study was to estimate the 1-year costs associated with treating diabetic macular oedema (DME) patients using current intravitreal anti-vascular endothelial growth factor (anti-VEGF) biologics compared with the dexamethasone implant. Methods: We conducted a descriptive cost-evaluation analysis using data from Oslo University Hospital and literature to compare three different intravitreal drugs for DME: bevacizumab, aflibercept and dexamethasone. Stratification of patients into 'Naive' o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…Even though some studies have suggested decreasing the frequencies of IVIs in this patient group, frequent use may be beneficial, depending on the drug administered. For instance, the dexamethasone implant has prolonged efficacy (an average of 3 injections per year), though it may require further visits to manage intraocular pressure-related issues [10,15,33,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Even though some studies have suggested decreasing the frequencies of IVIs in this patient group, frequent use may be beneficial, depending on the drug administered. For instance, the dexamethasone implant has prolonged efficacy (an average of 3 injections per year), though it may require further visits to manage intraocular pressure-related issues [10,15,33,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%